The impact of the application of the International Accounting Standard (IFARS 9) on the financial reporting of Iraqi private commercial banks - Qasim, Abo AL Hassan; Hasan, Ibrahim Naeem; Aljboory, Nassif Jassim (Utan Kayu Publishing, 2023)
The problem of recognizing credit losses is one of the most important contemporary problems in accounting thought, as the process of creating a provision for credit losses is one of the most important bases of measurement in hedging against these losses and mitigating their impact. Studies and research in the field of accounting show that the accounting treatment used in accordance with the international standard (IFRS 39) is one of the fundamental reasons for the exacerbation of the global financial crisis in 2008, which is the delay in the recognition of credit losses until they are achieved, which is the so-called model of actual credit losses, as the treatment is based onÂ recognizing the loss on the actual basis, i.e. after its occurrence, and not on the expected basis, i.e. before it occurs. In light of the criticisms leveled at the international standard (IAS 39) entitled Financial Instruments, the International Accounting Standards Board issued a standard for financial instruments, which is the International Financial Reporting Standard (IFRS 9). The new standard includes a proposed accounting framework for recognizing expected losses. According to the requirements of this standard, banks create provisions to face risks on an expected or estimated basis with the aim of early recognition of credit risks. As a result of the effects that this application will have on credit risks. It was necessary to shed light on the impact of the application of this standard on reducing credit risk, and thus the financial reporting of Iraqi commercial banks will be affected.